1997
DOI: 10.1159/000189583
|View full text |Cite
|
Sign up to set email alerts
|

Clearance Ratios of Amylase Isoenzymes and IgG Subclasses: Do They Reflect Glomerular Charge Selectivity?

Abstract: The clearance ratios of endogenous plasma proteins with the same size but a different charge, such as the amylase isoenzymes and the immunoglobulin (Ig) G subclasses, have been used to assess glomerular charge selectivity in man. These proteins are, however, subject to tubular reabsorption. In this study we measured the IgG subclass/IgG clearance ratios for IgG1 (pi 8.0-9.5), IgG2 (pI 7.0-7.5) and IgG4 (pI < 6) in 6 healthy volunteers. Our results suggested a selective influence of tubular reabsorption: the Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…Actually, previous study suggested that pI of IgG2 is 7.0 -7.5 (33), which was in accordance with VIII spot position (pI, ϳ7.3). The glycopeptide peak at m/z 2805.1, termed as IgG2 G0F1N (N, bisecting GlcNAc), in the GVIII spot spectrum, and peaks at m/z 2796.1 (IgG1 G1F1) and m/z 2805.2 (IgG2 G0F1N) in the LVIII spot spectrum, were higher than their corresponding peaks in NVIII spot spectrum, suggesting that part I may be a convenient approach for simplifying protein PTM study, attributed to the high-performance separation.…”
Section: Fig 3 Separation and Characterization Of Protein Complexessupporting
confidence: 66%
“…Actually, previous study suggested that pI of IgG2 is 7.0 -7.5 (33), which was in accordance with VIII spot position (pI, ϳ7.3). The glycopeptide peak at m/z 2805.1, termed as IgG2 G0F1N (N, bisecting GlcNAc), in the GVIII spot spectrum, and peaks at m/z 2796.1 (IgG1 G1F1) and m/z 2805.2 (IgG2 G0F1N) in the LVIII spot spectrum, were higher than their corresponding peaks in NVIII spot spectrum, suggesting that part I may be a convenient approach for simplifying protein PTM study, attributed to the high-performance separation.…”
Section: Fig 3 Separation and Characterization Of Protein Complexessupporting
confidence: 66%
“…However, a range of pH values (pH 5–7) was found to be suitable. When the extraction buffer approached the p I value of IgG1 (8–9.5; Buis et al ., 1997), less mAb was extractable. Interestingly, when the tobacco TSP levels were measured, the amount of TSP released at pH 7.4 was significantly higher than that at pH 6 ( P = 0.017) (Figure 8b).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the ratio of the clearance of IgG and IgG4 decreased in patients with minimal change disease, compatible with increased filtration of IgG4. 17 Still, we cannot exclude that these adjustments may cause an artificial correlation. We did, however, find a significant correlation between IgG4, but not IgG1 and IgG3, titers and the occurrence of spontaneous remissions.…”
Section: Discussionmentioning
confidence: 98%